Therapeutic Drug Monitoring of Amphotericin-B in Plasma and Peritoneal Fluid of Pediatric Patients after Liver Transplantation: A Case Series - Francesca Tortora; Luigi Dei Giudici; Raffaele Simeoli; Fabrizio Chiusolo; Sara Cairoli; Paola Bernaschi; Roberto Bianchi; Sergio Giuseppe Picardo; Carlo Dionisi Vici; Bianca Maria Goffredo (MDPI AG, 2022)
Fungal infections represent a serious complication during the post-liver transplantation period. Abdominal infections can occur following pre-existing colonization, surgical procedures, and permanence of abdominal tubes. In our center, liposomal amphotericin-B is used as antifungal prophylaxis in pediatric patients undergoing liver transplantation. The aim of this study is to evaluate peritoneal levels of amphotericin-B following intravenous administration. Six liver recipients received liposomal amphotericin-B. Three of them were treated as prophylaxis; meanwhile, three patients received liposomal amphotericin-B to treat Candida albicans infection. Plasma and peritoneal amphotericin-B levels were measured by LC-MS/MS in two consecutive samplings. Cmin (pre-dose) and Cmax (2 h after the end of infusion) were evaluated as drug exposure parameters for both plasma and peritoneum. Our results showed that peritoneal amphotericin-B levels were significantly lower than plasma and that the correlation coefficient was 0.72 (p = 0.03) between plasma and peritoneal Cmin. Moreover, although peritoneal levels were within the therapeutic range, they never reached the PK/PD target (Cmax/MIC > 4.5). In conclusion, PK exposure parameters could be differently used to analyze amphotericin-B concentrations in plasma and peritoneum. However, liposomal amphotericin-B should be preferred in these patients as prophylactic rather than therapeutic treatment for fungal infections.